2019
DOI: 10.1007/s13158-019-00244-5
|View full text |Cite
|
Sign up to set email alerts
|

Dialogues of Joy: Shared Moments of Joy Between Teachers and Children in Early Childhood Education Settings

Abstract: The study focuses on teachers' and children's shared moments of joy in early childhood education settings and contributes new knowledge in educational research by exploring joy as a relational rather than an individual phenomenon. The theoretical and methodological framework draws on a narrative approach and Martin Buber's dialogical philosophy. Data were gathered through video observations and diary notes in open ECE groups in Finland, with children from 2 to 6 years. The scenes of everyday life in ECE appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Photo-telling enables us to capturing related feelings about photos and the dialogical interactions that occur among children, photographs, places, and researchers. Other research has shown the dynamic and fragmentary nature of children's storytelling and how children fluently move from one topic to another while photo-telling (Karjalainen et al 2019;Puroila et al 2012a). Although we acknowledge that children's authentic experiences ultimately remain inaccessible, photo-telling can provide insights into what they find meaningful in their everyday lives in preprimary school.…”
Section: Photo-telling As a Methodological Approachmentioning
confidence: 99%
“…Photo-telling enables us to capturing related feelings about photos and the dialogical interactions that occur among children, photographs, places, and researchers. Other research has shown the dynamic and fragmentary nature of children's storytelling and how children fluently move from one topic to another while photo-telling (Karjalainen et al 2019;Puroila et al 2012a). Although we acknowledge that children's authentic experiences ultimately remain inaccessible, photo-telling can provide insights into what they find meaningful in their everyday lives in preprimary school.…”
Section: Photo-telling As a Methodological Approachmentioning
confidence: 99%
“…Findings in Ikegami and Agbenyega (2014) suggest that children's happiness should be the most important goal in any ECEC program and should thus have a prominent place in every early childhood curriculum. The work of Karjalainen et al (2019) found that joyful moments between teachers and children provided opportunities for conversational encounters that demand from teachers an attitude whereby every day moments are valued as ideal spaces for creating reciprocal relationships with children based on mutual respect. The findings of Ebbeck et al (2020) regarding how ECEC teachers can contribute to preparing their students for before, during and after any type of disaster are very interesting in this regard.…”
Section: Capturing Each Child's Voicementioning
confidence: 99%
“…Implications of this understanding are that there is no separation of entities prior to intra-action and that humans are not the only agentive actors in the research scene (see Sheridan et al, 2020). Some scholars have discussed the challenges in how to define joy and how to differentiate joy from other (positive) emotions or affects, and there is no generally accepted definition of joy in the research literature (see e.g., Karjalainen et al, 2019;Zembylas, 2007). We attended to affects as more than personal and individual feelings or emotions, rather like intensities that can amplify or diminish the capacity to act, and which emerge in encounters with (both human and nonhuman) others (Dernikos et al, 2020).…”
Section: Affective Literacies and Intensities In Early Childhood Educationmentioning
confidence: 99%
“…In the context of Finnish early childhood education, joy has attracted research attention. For instance, Karjalainen et al (2019), examined shared moments of joy between teachers and children as a relational rather than an individual phenomenon. The study shows that joyful encounters occur unexpectedly, and they require teachers to value the mundane moments as important spaces to create reciprocal, respectful relationships with children.…”
Section: Introductionmentioning
confidence: 99%